'Miracle cure' or 'liquid handcuffs': Reporting on naltrexone and methadone in the Australian print media. (18th March 2014) - Matthew‐Simmons, Francis; Ritter, Alison
Abstract Introduction and Aims The news media is an important source of information regarding new developments in medicine and public health interventions. Previous research has indicated that in many cases, reporting on new treatments can be inaccurate or sensationalist. This paper presents analysis of Australian print media reporting on two treatment options for heroin dependence (naltrexone and methadone). The aim of this study was to quantitatively compare the volume and content of Australian print media reporting on these two treatments, one of which had a long history of use in Australia, and the other which was comparatively newer. Design and Methods The study constituted a quantitative content analysis of a sample of 859 Australian newspaper articles, published over a 10‐year period (1997–2007). Each article paragraph was coded for positive outcomes/benefits of treatment, as well as negative outcomes associated with treatment. Results The analysis revealed that during this period, the Australian print media was significantly more likely to report the potential positive outcomes of naltrexone treatment, compared with the negative outcomes. In contrast, reporting on methadone focused more on the negative outcomes and side effects. Discussion and Conclusions The relative frequency by which the benefits of naltrexone were mentioned in this sample of news content is somewhat at odds with the extant efficacy and effectiveness research evidence. The findings suggest that reporting on these treatments in the Australian print media has not been balanced. This type of reporting has potential implications for public attitudes, as well as policy decisions. [Matthew‐Simmons F, Ritter A. 'Miracle cure' or 'liquid handcuffs': Reporting on naltrexone and methadone in the Australian print media. Drug Alcohol Rev 2014;33:506‐514]